The effects of gabapentin and ethanol on the regulated cell death of astrocytes in primary culture: Učinki gabapentina in etanola na regulirano celično smrt astrocitov v primarni kulturi - Hutyrová, Paulína; Stangelj, Jan; Lipnik-Štangelj, Metoda (Acta Medico-Biotechnica, 2021)
Purpose: In this study, the effect of gabapentin on the regulated cell death of astrocytes in primary culture was examined. Because astrocytes are relatively resistant to decay by apoptotic pathways, the effect of different concentrations of gabapentin on apoptosis in necroptosis was tested as another form of regulatedcell death. In addition, the impact of gabapentin on the death of astrocytes that were exposed to ethanol was also examined.Methods: Primary cultures of astrocytes that were obtained from the brain cortex of newborn rats were used as the experimental model. Cells were exposed to different concentrations of gabapentin only, ethanol only or to a combination of ethanol and gabapentin. Using flow cytometry, the proportions of viable, early apoptotic, necroptotic, and secondary dead cells were determined.Results: The effect of gabapentin on early astrocytic apoptosis and necroptosis was dependent on concentration. In concentrations of up to 10 μg/mL, gabapentin did not affect astrocyte deaths; whereas at higher concentrations, the proportion of necroptotic cells increased. The concomitant exposure of the cells to gabapentin (10 μg/mL) and ethanol (100 mM) for 24 hours did not significantly affect cell death caused by ethanol. For cells that are exposed to 50 mM ethanol for 7 days, gabapentin slightly reduced the proportion of necrotic cells.Conclusion: Gabapentin did not affect the viability of astrocytes in concentrations up to 10 μg/mL. The concomitant exposure of astrocytes to ethanol and gabapentin for 24 hours did not reduce the toxicity of ethanol. In astrocytes that are chronically exposed to ethanol, gabapentin slightly reduced the effect of ethanol on necroptosis.
Keywords: gabapentin; ethanol; atrocytes; cell death